Electric sounds technological change and the rise of corporate mass media - Wurtzler, Steve J.; Gale Group (New York Columbia University Press, 2007)
Focuses on the innovations in the electronic production and transmission of sound in the 1920s and '30s and their explosive impact on the American mass media, especially the radio, the phonograph, and the cinema.
Technological innovation and the consolidation of corporate power -- Announcing technological change -- From performing the recorded to dissimulating the machine -- Making sound media meaningful: commerce, culture, politics -- Transcription versus signification: competing paradigms for representing with sound -- Conclusions/reverberations.
Electronic reproduction.
Keywords: Mass media -- Technological innovations -- United States -- History -- 20th century; Mass media -- Ownership -- United States -- History -- 20th century; Sound -- Recording and reproducing -- History -- 20th century; Mass media and history -- United States; Radio -- History; Phonograph -- History; Motion pictures -- History; Electronic books